THREATENED MEDICINAL PLANTS OF SOUTH AFRICA: CASE OF THE FAMILY HYACINTHACEAE - Xego, S.; Kambizi, L.; Nchu, F. (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Traditional medicine plays a major role in the primary health care of many people living in rural areas. South Africa is a home to over 30,000 species of higher plants and 3,000 of these species have been found to be used in traditional medicine across the country. South African medicinal plants are decreasing at an alarming rate as a result of over exploitation. Today many medicinal plants face extinction but detailed information is lacking. The purpose of this paper was to review current and proposed cultivation strategies that could be used to improve plant conservation statuses, livelihoods of the people involved in medicinal plant industry and sustainability of this industry. Methods: In this review, emphasis was on the members of Hyacinthaceae family and the species Siphonochilus aethiopicus (Schweinf) B.L. Burtt (Zingiberaceae), which are some of the most traded and used in traditional herbal medicine. Detailed literature search was conducted on the current strategies that are being used for the cultivation of medicinal and food crops and a conceptual analysis of how technologies used for the cultivation of non-medicinal crops could be adopted for cultivation of medicinal plants in Africa. Siphonochilus aethiopicus was used as a case study to demonstrate the potential of using alternative cultivation strategy such as hydroponics in the cultivation of medicinal plants. Results: The results showed that hydroponics has the potential to improve plant growth. In conclusion, evidences suggest that there is potential for growth in the medicinal plant industry if optimum cultivation technologies such as hydroponics are implemented despite the perception that Africans have an ingrained traditional preference of wild harvested plants, on the contrary many Africans have no issues with cultivated medicinal plants.